Managing phosphate rock to improve nutrient uptake, phosphorus use efficiency, and carrot yields - Mwangi, E.; Ngamau, C.; Wesonga, J.M.; Karanja, E.; Musyoka, M.W.; Matheri, F.; Fiaboe, K.; Bautze, D.; Adamtey, N. (Springer, 2020)
The objectives of this study were to assess (a) the efficiency of lemon and pineapple juices and the concentration and time needed to release more than 50% of available phosphorus from phosphate rock (PR), and (b) the effect of different types of PR management on carrot yields, nutrient uptake, and phosphorus use efficiency. Field trials were set up at two sites with humic andosols and orthic acrisols over two seasons in Kenya. In a randomized complete block design, replicated three times, the following treatments were compared: (i) composted dissolved PR in lemon juice; (ii) powdered PR composted; (iii) dissolved PR in lemon juice added to compost; (iv) powdered PR and compost; (v) triple superphosphate and compost; (vi) compost alone; (vii) triple superphosphate and Tithonia diversifolia mulch; with (viii) un-amended soil as a control. Lemon juice was effective in solubilizing PR, releasing 63% of the total phosphorus applied into available phosphorus, compared to 11% for pineapple juice and 6% for water. The combined application of compost and PR dissolved in lemon juice at planting significantly increased phosphorus and potassium uptake, phosphorus use efficiency, and carrot yields that was comparable to the use of triple superphosphate and compost. The study concludes that the dissolution of phosphate rock with lemon juice at a ratio of 1:5 phosphate rock to lemon juice and its combined application (immediately after dissolution) with compost at planting improves nutrient uptake, phosphorus use efficiency, and crop yields. We recommend further studies to explore the possibility of using citrus peels or other acidic organic materials to enhance the solubility of phosphate rock, and to assess their practical feasibility and the economic advantage(s) in the large-scale production of high value crops.